A Novel Presentation of Cutaneous Angiosarcoma: A Case Report and Review - Bajaj, Sonali; Sharma, Prafulla Kumar; Sachdev, Imroz Singh; Bhardhwaj, Minakshi (Indian Journal of Medical and Paediatric Oncology, 2017)
We report a case of a 70-year-old male, with slowly widening induration, ulceration, and oozing for 3 months on the scalp and face. The diagnosis of aggressive cutaneous angiosarcoma was made on histopathology and immunochemistry from the biopsy material from the involved area of the skin.
Keywords: CD31+; CD34+; cutaneous angiosarcoma; mimicking cellulitis; vimentin